EPIDEMIOLOGIC PROFILE OF MEN HOSPITALIZED WITH BREAST CANCER IN BRAZIL - Grando, Gabriel Fiorio; Bastos, Juliano Peixoto (Mastology, 2021)
Introduction: Breast cancer is the most common type of cancer among women worldwide and in Brazil, just after non-melanoma skin cancer. Breast cancer can also occur in men, although being rare, representing 1% of the total number of notifications of the disease. Due the rarity of this pathology, little is known about the etiology of male breast cancer, but some risk factors such as advanced age, hormonal imbalance, and family history have been pointed out. Objectives:This study’s objective was to understand the epidemiologic profile of the men hospitalized due breast cancer in Brazil in the previous five years. Methods:This is a descriptive study of secondary data, which were gathered using the IT Department of the Brazilian Unified Health System, and it corresponds to the cases registered from January 2016 to December 2020. The data of interest were those related to the total number of admissions, age range, ethnicity, mortality rate, average amount spent in each hospitalization. Results: There were 3,501 (100%) admissions in Brazil due to male breast cancer. In the Southeast, there were 1,439 (41.1%) hospital admissions, being this the part of the country with the majority of hospi- talized men. Followed by this region are the Northeast (26.7%), the South (18.1%), the Midwest (8.3%) and the North (5.7%). The year showing most notifications was 2019, with 832 hospital admissions (23.7%). The other years under review do not show significant changes in the number of admissions. The predominant age group was between 60 to 69 years (26.5%), followed by 50–59 (21.5%), 70–79 (19.9%) and 40–49 years (13.4%). Regarding ethnicity, white and brown men had similar notifications, 1,326 (37.8%) and 1,248 (35.6%) respectively. The remaining percentage is for not registered (20.1%), blacks (5.0%), yellow (1.4%) and indigenous (0.02%). The mean length of hospital stay for men with breast cancer was 4.3 days, ranging from 3.0 to 5.5 across the regions. The mortality rate was 9.40% in Brazil. Regarding the regions, the Northeast showed the highest mortality rate, 14.50%. The average amount spent on each hospitalization was R 1,917.70 (USD 354,74, approximately). Conclusions: In Brazil, the mortality rate of men due to breast cancer is higher than the mortality rate of women with breast cancer, which is 8.44%. Therefore, the prognosis for male and female breast cancer is similar, but the overall survival rates are lower for males due to older age and advanced stage at diagnosis. Patients and health providers should pay attention to the existence of breast cancer in men and its known risks factors. Also, at last, many patients receiving hormonal therapy as a treatment for other diseases (eg., prostate cancer) should be aware of its side effect of the development of breast cancer in men.